A dynamic homogenization method for 3D core calculations. (15th September 2021) - Galia, Antonio; Sanchez, Richard; Zmijarevic, Igor
Highlights: A new dynamic homogenization approach for 3D core calculations. Equivalence theory and Flux Discontinuity Ratio techniques have been applied to reference homogenization problems with non-zero surface leakage. We tested the methodology on a PWR MOX/UOX heterogeneous 3D configuration. The new method shows improved accuracy of the pin power over the classical two-step calculation scheme. Abstract: Three-dimensional deterministic core calculations are typically based on the classical two-step calculation scheme. The sizable number of approximations introduced in this approach can easily reduce the accuracy of the low-order operator solution, especially in high heterogeneous configurations. Several techniques have been developed in order to overcome these limitations, including direct approaches that make extensive use of computational resources, such as the 2D/1D Fusion method and direct 3D transport calculations. In this work we propose the method of Dynamic Homogenization as an alternative technique for 3D core calculations that lies between the classical and the direct approaches in terms of accuracy and performance. The methodology consists in an iterative process between core and assembly calculations that provides a set of homogenization parameters for the low-order operator, taking into account the actual environment of each assembly in the core. This is mediated defining a set of 2D reference homogenization problems that are solved with imposed core eigenvalue, fixed incoming boundary source and a simplified axial leakage expressed as a volumetric source. The methodology eliminates the infinite lattice approximation and the critical leakage model, and offers the advantage of avoiding off-line calculations, cross-section interpolations, power reconstruction techniques and expensive 3D transport calculations. The NEA "PWR MOX/UO2 Core Transient Benchmark" was chosen for our analysis where we compare the accuracy and the performance of the two-step and the Dynamic Homogenization calculations against the direct 3D transport solution. We analyzed two different core configurations: an axially uniform core and a partially rodded core.